Understanding English Phonology: A Beginner's Guide - Yani Lubis; Ela Carmelia Mukti Sambas; Gilang Hizbullah (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
The purpose of this research is to provide understanding of English phonology to the learners who are new with English phonology. The method used in this research is literature review. This discussion explores the study of English sounds, known as English phonology. It covers important topics for beginners, such as understanding the basic units of sounds (phonemes) and their variations (allophones). The chat also introduces processes like assimilation, dissimilation, and deletion that affect how sounds change in spoken English. Additionally, it explains vowel and consonant reduction, which impact how certain sounds are pronounced. Lastly, the chat provides an overview of classifying consonant and vowel sounds based on their characteristics. By learning about these aspects, beginners can improve their pronunciation, understand different sound patterns, and enhance their overall communication skills in English.